Increasing the Softskill of Youth Dropout School in the Coastal Ecotourism Tapak Paderi City of Bengkulu through Education on Turtle Conservation and Making Marine Reading Houses (RUBAH) - Eko Sumartono; Merlian Zikri; Ari Anggoro; Ridha Rizki Novanda; Anandyawati Anandyawati; Amir Husaini K. Amrullah (Comment: an International Journal of Community Development, 2018)
The development of preservation of the turtle ecotourism area at Tapak Paderi Beach by increasing the skill and innovative soft skills for out-of-school youth is the goal achieved in this community service. Through the Appreciative inquiry methods approach with the stages of team coordination, turtle counseling socialization and education, the introduction of basic welding techniques, making RUBAH and turtle aquascape. Overall results achieved are the implementation of socialization activities, training and guidance for school dropouts besides being realized in the implementation of basic techniques of small library welding (RUBAH), turtle aquascape making and broken youths to become tourist education guides for domestic and foreign tourists.